METODE ELEMEN HINGGA UNTUK MASALAH SYARAT BATAS DARI OPERATOR DIFERENSIAL POSITIF - sutrima, sutrima (MATEMATIKA, 2002)
The purpose of this research is to investigate numerical solutions of boundary value problems of positive differential operator by finite-element methods. The results showed that the finite-element methods can be implemented to obtained numerical solutions of boundary value problems of second-order positive differential operator. Moreover, rate of convergence of Ritz finite-element with Lagrange quadratic interpolation be in the the -norm and in the energy norm.